Experiencing Shared Decision Making in Interprofessional Teams: A Case Study - Deckers, Stijn R. J. M.; Makauskienė, Vilma; van Zaalen, Yvonne (Pedagogika, 2024)
Shared decision-making is one key element of interprofessional collaboration. Communication is often considered to be the main reason for inefficient or ineffective collaboration. Little is known about group dynamics in the process of shared decision-making in a team with professionals, including the patient or their parent. This study aimed to evaluate just that. Simulation-based training was provided for groups of medical and allied health profession students from universities across the globe. In an overt ethnographic research design, passive observations were made to ensure careful observations and accurate reporting. The training offered the context to directly experience the behaviors and interactions of a group of people. Overall, 39 different goals were defined in different orders of prioritizing and with different time frames or intervention ideas. Shared decision-making was lacking, and groups chose to convince the parents when a conflict arose. Group dynamics made parents verbally agree with professionals, although their non-verbal communication was not in congruence with that. This research has shown that the outcome and goalsetting of an interprofessional meeting are highly influenced by group dynamics. Also, the vision, structure, process, and results of the meeting are affected by multiple inter- or intrapersonal factors.